The Quest For Women Political Empowerment In Nigeria: The Role Of Mass Media - Ajayi, A. T. (Advances in Social Sciences Research Journal, 2018)
This work derived its strength from secondary and primary sources. Women empowerment in Nigeria is a much debating theme and a harbinger of hard task as one have to recognize the reality of gender isolated issues and discrimination against women as social perniciousness since several years back. Empowering women aims to inspire women with the courage to break free from the chains of limiting self belief patterns and societal or religious conditioning that have traditionally kept women suppressed and unable to see their true beauty and power. Mass media plays one of the huge parts in women’s improvement and its empowerment. Media can make an enlivening motivation to accomplish their potential as prime movers of progress in the public eye. Mass media will be engaged as one of the boss imperative elective necessities in helping the women empowered. It will help as the best means and access to stand in opposition to the mistreatment and underestimation of women at the grass root level. Along these lines, this examination will uniquely feature the positive viewpoints of mass media as a formative apparatus to depict and reverberates the perspectives and thoughts of women in Nigeria. The paper however derives its strength from both primary and secondary sources.